The Notary Role in Making a Deed of an Electronic Sale-Purchase Agreement - Ragil Ridho Dewanto; Setyawati Setyawati; Arpangi Arpangi; Peni Rinda Listyawati (Sultan Agung Notary Law Review, 2022)
The purpose of this research is to analyze and find out: 1). The role of the Notary in making the deed of the sale and purchase agreement based on Act No. 25 of 2009 concerning Public Services. 2) Constraints and solutions in making a Notary Deed electronically. The method used in this study is the juridical-normative method, the specifications in this study are descriptive analysis, the data used are primary data and secondary data, using data collection with library studies and field studies, qualitative data analysis, problems analyzed by authority theory and legal certainty. The results of this study indicate that: 1) The role of a notary in making a deed of sale-purchase agreement based on Act No. 25 of 2009 concerning Public Services is to authenticate electronic-based documents, which authentication documents can be printed out anywhere, anytime. Notaries also play a role in providing certainty to the parties when conducting transactions completely on their own consciousness and without any coercion or threats to sign electronic-based documents. In this cyber notary, the difference is in terms of facing. So far, facing is done by being physically present but facing in relation to a cyber notary is done by using electronic media, such as teleconference or video call. 2) Obstacles and solutions in making Notary Deeds electronically, namely the absence of laws governing cyber notaries in Indonesia such as in developed countries, is an obstacle for Notaries to take one step further in order to create good, effective, efficient, and safe public services.